The Singing of the New World: Indigenous Voice in the Era of European Contact - Tomlinson, Gary (Cambridge (UK) Cambridge University, 2007)
In The Singing of the New World Gary Tomlinson offers histories of ancient music long since silent: the songs of the Indians that Europeans met in the sixteenth century. Merging recent cultural history, early European accounts, archaeological findings, and rare indigenous documents for the Mexica (or Aztecs), the Incas, and the Tupinamba of lowland Brazil, Tomlinson explores the place of singing in these societies. He details the expressive and ritual ends it was expected to fulfil before and after the coming of the conquistadors. Musical practices and the cultural ends they served come alive across a spectrum that reaches from the cosmogonic geometry of Inca ritual song through the imminent sacred materiality of Mexican cantares to the intricate interconnections of singing, speaking and eating in Tupinamba cannibalism. A final chapter considers the fears mutually and repeatedly inspired by the expressive powers of American and European song.
Keywords: Music history; Cuckoo; Singing; Ethnomusicology